Disposition kinetics of gentamicin in normal and febrile goats following single dose intramuscular administration - AHMAD, A H; SHARMA, L D (The Indian Journal of Animal Sciences, 2013)
A study of the disposition kinetics of gentamicin was conducted in goats following single dose im administration (5 mg/kg). The effect of fever (induced by E. coli endotoxin) was observed on absorption, distribution and elimination of gentamicin. Serum concentrations of gentamicin Were detectable up to 6 hr in both groups of goats. Significant differences in serum concentrations of gentamicin were not observed at any time after injection between 2 groups of animals. The data were adequately described by a one- compartment model both in normal and febrile goats. Elimination half-life of 104.8 min in fertile goats was calculated. The volume of distribution (V d/F) was 192.5 ml/kg in febrile goats whereas in normal goats it was 158.0 ml/kg. Based on these pharmacokinetic parameters a dosage regimen for gentamicin was calculated.